Pengaruh Literasi Keuangan Dan Inklusi Keuangan Terhadap Kinerja UMKM Di Bira Kabupaten Bulukumba - Sarfiah, Sarfiah; Wa Ode Rayyani; Alamsjah, Alamsjah (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to determine the influence of financial literacy and financial inclusion partially on the performance of Micro, Small, and Medium Enterprises (MSMEs) in Bira, Bulukumba Regency. The background of this study is based on the low level of literacy and financial access in some MSME actors, which has the potential to affect the effectiveness of their business management. The method used is a quantitative approach with a survey technique. Data were collected through questionnaires distributed to 122 respondents from a total population of 176 MSMEs, with sample determination using the Slovin formula. Data analysis was carried out using multiple linear regression tests. The results of the study showed that financial literacy has a positive effect on MSME performance. MSME actors who have a good financial understanding tend to be more capable of managing capital, planning finances, and making business decisions appropriately. In addition, financial inclusion also has a positive and significant effect on MSME performance. Access to formal financial services such as savings, business loans, and digital transaction facilities has been proven to help business actors in running operations and developing their businesses. This finding shows that increasing financial literacy and access to formal financial services need to be a priority in the MSME empowerment strategy in Bira, Bulukumba Regency.